Diabetes and plant‐derived natural products: From ethnopharmacological approaches to their potential for modern drug discovery and development. (9th September 2020) - Jugran, Arun K.; Rawat, Sandeep; Devkota, Hari P.; Bhatt, Indra D.; Rawal, Ranbeer S.
Abstract : Diabetes is a disease of serious concern faced by the health care industry today. Primary diabetes mellitus and its complications are still costly to manage with modern drugs. Extensive research on the screening of anti‐diabetic agents in past decades established natural products as one of the major potential sources of drug discovery. However, only a few drugs of plant origin have been scientifically validated. Therefore, the development of new anti‐diabetic drugs is of great demand. Hence, natural products could be explored as potential anti‐diabetic drugs. Natural plants derived extracts and molecules like berberine, ginsenosides, curcumin, stevioside, gingerols, capsaicin, catechins, simple phenolic compounds, anthocyanins, resveratrol, genistein and hesperidin obtained from different species are used for curing diabetes and found to possess different action mechanisms. In this review, the importance of medicinal plants and their active constituents for anti‐diabetic agents are described. The present study also emphasized the importance of diabetes control, reduction in its complications and use of the anti‐diabetic agents. The detailed action mechanism of these extracts/compounds for their activities are also described. However, the anti‐diabetic drugs from plant origin require scientific validation through animal and clinical studies to exploit in terms of modern commercial medicines.